Sistem Pendukung Keputusan Guru Berprestasi Berbasis Java Desktop Dengan Penggabungan Metode SAW dan Topsis - Rahardhiyan Wahyu Putra; Mustika Mentari (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2020)
A decision support system is a system that is able to provide problem solving and communication skills for problems with semi-structured and unstructured conditions. The recommendation system is related to the decision-making process. In the current global era, the position of the teacher as educator plays an important role in the process of teaching and learning and enhances student achievement in academic and non-academic fields. award or reward as a teacher. Based on this, it is necessary to define a model for identifying outstanding teachers based on software engineering, to develop applications that can be applied to very complex tasks. This system was developed using a combination of the SPK method, namely simple additive weighting (SAW) and TOPSIS. With the SPK, this can help determine the selection of teachers with achievements in a relatively faster time with relatively more accurate results.